2019
DOI: 10.1002/jgf2.249
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of the emergency department for nonurgent conditions: Patient characteristics and associated factors at a Japanese hospital

Abstract: Background The purpose of this study was to investigate the primary factors associated with inappropriate out‐of‐hours emergency department ( ED ) use by patients with nonurgent conditions. Methods We compared patients with nonurgent conditions who made inappropriate, out‐of‐hours ED visits to patients who visited an acute care hospital during daytime consultation hours between May 30 and October 16, 2014, in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Inappropriate use of ED for non-emergency conditions is a problem in terms of overcrowding of emergency facilities, unnecessary testing and treatment, increased medical costs, burden on medical service providers and weaker relationships between patient and primary care provider. Studies evaluating this phenomenon have found that the inability to take time off from school or work during the day and the ease of use of emergency care without the need for an appointment are cited as a reason for their consultation by a significant percentage of patients, suggesting that inappropriate use of ED could be a matter of personal convenience [14,15]. An observational study investigated the factors associated with ED visits for headache and found that the most common reason for visiting ED was a perceived emergency condition or referral by a physician (33.3%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate use of ED for non-emergency conditions is a problem in terms of overcrowding of emergency facilities, unnecessary testing and treatment, increased medical costs, burden on medical service providers and weaker relationships between patient and primary care provider. Studies evaluating this phenomenon have found that the inability to take time off from school or work during the day and the ease of use of emergency care without the need for an appointment are cited as a reason for their consultation by a significant percentage of patients, suggesting that inappropriate use of ED could be a matter of personal convenience [14,15]. An observational study investigated the factors associated with ED visits for headache and found that the most common reason for visiting ED was a perceived emergency condition or referral by a physician (33.3%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate use of ED for non-urgent conditions is a problem in terms of crowding emergency facilities, unnecessary testing and treatment, increased medical bills, burden on medical service providers and weaker patient-primary care provider relationships. Studies evaluating this phenomenon found that inability to take time off from school or work during the day, the ease of use of emergency care and the non-necessity for an appointment are indicated as a reason for their consultation by a significant percentage of patients, suggesting that inappropriate use of ED could be a matter of personal convenience [13,14]. An observational study investigated the factors associated with ED visits for migraine and found that the most common reason for visiting ED was a perceived emergency condition or referral by a physician (33.3%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some factors associated with inappropriate ED usage were not studied. A recent study in a Japanese hospital found that having two or more prior out-of-hours ED visits in the past 3 years was identified as a factor [14].…”
Section: Discussionmentioning
confidence: 99%
“…These visits are all the more “inappropriate” because the majority of them occur during the business hours of most primary care providers (PCP) [10], for the most part at the sole initiative of the patient [1,2,11,12,13]. Personal convenience and ease of emergency care use were listed as motivations for consulting ED in several countries, such as Japan [14], the United States [15], and Spain [16]. This influx of non-severe patients does not benefit from the holistic management that a general practice provides and it increases the already growing number of ED consultations caused by an aging population and a rise in chronic illnesses [17].…”
Section: Introductionmentioning
confidence: 99%